Nieczytelność i nieprzezroczystość. Dwa wymiary wizualności tekstu - Depcik, Dominika (Humaniora. Czasopismo Internetowe, 2020)
This work deals with the visuality of the text, in the context of two paths of a reflection on its being: the illegibility/ legibility and transparenty/ opacity. Its aim is to prove, that the text is a visual medium. The first part of the work introduces the main topic by providing a short outline of the history of subject matter, which is typography, the area of visual communication that works with the text. The second part deals with the analysis of the text in terms of aforementioned paths of reflection. The issue of transparenty had to be claryfied first, because firstly it should be proven, that the text is not invisible for an eye. From this matter the work passes to the notion of illegibility: if the text is not transparent – visually neutral – but instead, highly graphically characterised, then the question is, if it does remain readable.